Some Aspects Related To The Procedural Order Of Fixing Evidence-Based Information In Digital Media - Muzaffar Muminov (The American Journal of Political Science Law and Criminology, 2020)
The article analyzes some issues related to the procedural order of collecting, fixing, and consolidating evidence information obtained using digital photography, video recordings and audio recordings.